Incorporation of Some Eicosaenoic Acids into Endothelial Cells – Effect on Platelet Inhibitory Activity and Prostacyclin Production - Sicard, Béatrice; Lagarde, Michel (Thrombosis and Haemostasis, 1985)
Primary cultures of endothelial cells from human umbilical veins were grown until confluency. Then, dihomogammalinolenic acid (DHLA or 20:3n-6) and eicosapentaenoic acid (EPA or 20:5n-3), precursors of monoenoic and trienoic prostanoids, respectively, as well as 5,8,11-eicosatrienoic acid (20:3n-9), and isomer of DHLA, were incorporated into endothelial lipids. DHLA-rich endothelial cells had a decreased capacity of prostacyclin production. By contrast EPA- or 20:3n-9-rich endothelial cells were comparable to controls in this respect. DHLA and EPA were efficiently acylated into cell phospholipids and triglycerides at the opposite of 20:3n-9. It is suggested that both DHLA and EPA could alter the liberation of endogenous arachidonic acid for prostacyclin synthesis but this might be counterbalanced in EPA-rich endothelial cells by PGI3 production. We conclude that DHLA enrichment of endothelial cell lipids may impair the possible beneficial effect of the acid upon platelet functions whereas that of EPA would not be modified.
Keywords: Endothelial cells; Prostacyclie; Platelet inhibitory activity; Eicosaenoic acids